(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The paper describes the studies performed to clerify the relationships that exist, between the wings development and diet of the P. ramburi, which commonly exists in a micropterous form. Laboratory tests, which has been performed giving food consisting only of mold or of a partially mold grown substratum, demonstrated that the insect has a mycetophagous diet. The insects survival during its young stages and its postembryonal growth is certainly influenced by the type of molds used as food. Macroptera specimens are merely found in breedings, which are basically supplied with fungus mycelium and above all of Penicillium sp., Aspergillus versicolor and Alternaria tenuis.